correct answer is -6 hope this helps!

Simplify the left side. Simplify each term. Apply the distributive property. 2 + ( − 3 x − 3 ⋅ 4 ) = 8 2 + - 3 x - 3 ⋅ 4 = 8 Multiply − 3 - 3 by 4 4 to get − 12 - 12 . 2 + ( − 3 x − 12 ) = 8 2 + - 3 x - 12 = 8 Simplify the expression. Remove unnecessary parentheses. 2 − 3 x − 12 = 8 2 - 3 x - 12 = 8 Subtract 12 12 from 2 2 to get − 10 - 10 . − 3 x − 10 = 8 - 3 x - 10 = 8 Move all terms not containing x x to the right side of the equation. Since − 10 - 10 does not contain the variable to solve for, move it to the right side of the equation by adding 10 10 to both sides. − 3 x = 10 + 8 - 3 x = 10 + 8 Add 10 10 and 8 8 to get 18 18 . − 3 x = 18 - 3 x = 18 Divide each term by − 3 - 3 and simplify. Divide each term in − 3 x = 18 - 3 x = 18 by − 3 - 3 . − 3 x − 3 = 18 − 3 - 3 x - 3 = 18 - 3 Simplify the left side of the equation by cancelling the common factors. x = 18 − 3 x = 18 - 3 Divide 18 18 by − 3 - 3 to get − 6 - 6 . x = − 6